Islamic Educational Values in the Pa’seka Manyiang Tradition - Umarella, Samad; Lasaiba, Irvan (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
This research is a qualitative study using observation, interviews, and documentation as data collection techniques, while the data analysis involves steps of data reduction, data examination, and drawing conclusions. The findings reveal that the implementation of the Pa’seka Manyiang traditional ceremony in Negeri Tulehu aligns with Islamic teachings, although it incorporates local customs and traditions. The process consists of three stages: preparation, which includes activities such as Kumpul Basudara (gathering relatives), fundraising, and logistical arrangements; implementation, which involves delivering Hikmah Maulud (sermons), collective prayers, dhikr, and blessings upon the Prophet; and closing, which features family entertainment like Sawat dancing and site cleanup. Each stage reflects Islamic educational values, including worship values like charity, ethical values such as fostering relationships and mutual respect, devotional values like dhikr and enjoining good, and faith values like prayer and remembrance of Allah.